Humanitarian diplomacy and the countries of the Global South: Trends and discourses - D. A. Kuznetsov; V. A. Dmitrieva (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In recent years, discussions about the essence of humanitarization and humanization of international relations have intensified due to the aggravation of economic, social, and ethical problems against the background of a sharp deterioration in the international situation, particularly in the Global South. This paper aims to identify the specifics and provide a comparative analysis of the approaches of both the developed and developing states of the North and the South to the formats, content and purpose of humanitarian diplomacy in contemporary world politics. The first section examines academic discussions on the issues of humanitarian diplomacy. The authors highlight two main approaches in foreign and Russian international political studies to addressing the humanitarian problems of the Global South — an objectal and a subjectal ones. The former is typically associated with the developed countries of the Global North and is rooted in the practices of the colonial era. The latter gained prominence in academic research in the 21st century with the emergence of the ‘new donors’, which promoted joint development programs led by the countries of the Global South and built on regional financial institutions. At the same time, the authors note that academic research tends to focus primarily on the dynamics of aid flows and conditions for development assistance, while a number of current trends in the humanitarian diplomacy remain understudied. These trends are examined in the second section of the article. The authors emphasize the growing trend towards transnationalization and privatization of humanitarian diplomacy, active involvement of non-state and hybrid actors. The third section outlines the key features of humanitarian diplomacy of the leading countries of the Global South (China, India, Turkey), as well as that of the ASEAN states and Arab monarchies. The authors identify several general principles of humanitarian diplomacy shared by the countries of the Global South: a broad, pluralistic understanding of the humanitarian agenda to include cultural, scientific, academic, and youth policy issues; commitment to the ideas of solidarity and humanitarian cooperation (instead of the donor-recipient model); normative neutrality of the humanitarian policy; adherence to the principles of state sovereignty.